Serum Thrombopoietin (TPO) Levels in Patients with Amegakaryocytic Thrombocytopenia Are much Higher than those with Immune Thrombocytopenic Purpura - Mukai, Harumi Y; Kojima, Hiroshi; Todokoro, Kazuo; Tahara, Tomoyuki; Kato, Takashi; Hasegawa, Yuichi; Kobayashi, Toshitaka; Ninomiya, Haruhiko; Nagasawa, Toshiro; Abe, Tsukasa (Thrombosis and Haemostasis, 1996)
We assayed serum thrombopoietin (TPO) levels in amegakaryocytic thrombocytopenia (AMT) and immune thrombocytopenic purpura (ITP) patients by using a newly established enzyme-linked immunosorbent assay (ELISA). TPO levels in AMT patients were quite high (mean ± SD = 13.7 ± 11.2 fmoles/ml, n = 4), whereas those in ITP patients were only slightly higher (1.25 ± 0.39, n = 12) than those of the healthy donors (0.55 ± 0.2, n = 20). Furthermore, in ITP patients no correlation was observed between platelet counts and serum TPO levels (correlation coefficient = 0.14). We further assayed serum TPO levels sequentially during steroid treatment in patients with AMT and ITP. In one AMT patient serum TPO levels started to decrease in accordance with the increase of megakaryocyte counts, which preceded the increase in platelet counts. However, in ITP patients serum TPO levels did not change significantly throughout the course of the treatment despite the recovery of platelet counts. Based on these findings, we conclude that serum TPO levels may be regulated at least in part by megakaryocyte counts.